Restoring the Balance: First Nations Women, Community, and Culture - Rodríguez de France, María del Carmen (International Indigenous Policy Journal, 2010)
With empowering stories and histories from twelve Aboriginal women who are leaders in different contexts and communities, the book acknowledges and celebrates the contributions of Aboriginal women to diverse fields of work and disciplines such as art, culture, politics, language, law, community, education, and social activism. About the Authors Eric Guimond is an assistant director at the Strategic Research and Analysis Directorate at Indian and Northern Affairs Canada. Gail Guthrie Valaskakis was a Distinguished Professor Emeritus of Concordia University and was a leading authority on Aboriginal Media and Communication. She passed away in 2007. Madeleine Dion Stout is a former nurse and founding director of the Centre of Aboriginal Education, Research, and Culture at Carleton University.